Kepemimpinan Etis,Apa Itu dan Mengapa Itu Penting? - Viona Rahmawati Jubaidah; Anniez Rachmawati Musslifah (Politeknik Kampar, 2024)
The research aims at exploring the influence of ethical leadership on employees’ behaviors on an individual level. It first studies the research that has been done on ethical leadership in order to provide an overview, and then explores the potential outcomes triggered by the phenomenon on employees’ behaviors. A quantitative analysis was employed with a survey of 131 respondents realized via emailing and social media.The study suggests that ethical leadership influences different variables both positively and negatively. One the one hand, it influence positively related with moral awareness, job satisfaction, motivation, and prosocial behaviors. On the other hand, ethical leadership is negatively related with organizational misbehaviors and counterproductive work behaviors.